Serum Bilirubin Level Is Increased in Metabolically Healthy Obesity - Fu, Jing; Wang, Qiu; Zhang, Lin; Liu, Jia; Wang, Guang (Frontiers in Endocrinology, 2022)
Objectives: Bilirubin is a biochemical substance with metabolic benefits. The objective of this research was to elucidate the association between serum bilirubin levels and metabolic alterations in different obesity phenotypes. Methods: In total, 1,042 drug-naive participants were included in the study. Of them, 541 were obese patients and 501 were age-matched and sex-matched healthy control subjects. The obese patients were divided into metabolically healthy obesity (MHO) group and metabolically unhealthy obesity (MUHO) group according to the levels of fasting plasma glucose (FBG), triglyceride (TG), high-density lipoprotein cholesterol (HDL-C) and blood pressure (BP). Clinical and biochemical parameters including total lirubin (TBil), indirect bilirubin (IBil) and direct bilirubin (DBil) were measured. ANOVA or Kruskal-Wallis H test was used to test differences among the three groups. Pearson and Spearman correlations were used to analyze the relationships between two parameters. The relationships between bilirubin and other variables were analyzed using Multivariate regression analysis. Results: MHO group had favorable blood pressure, glucose and lipids profiles, along with increased TBil and DBil, and decreased high-sensitivity C-reactive protein (hsCRP) and homeostasis model assessment of insulin resistance (HOMA-IR) levels when compared to MUHO group (P < 0.05 for all). TBil and DBil were negatively correlated with total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), fasting insulin (FINS), hsCRP and HOMA-IR, even after adjusted for age, gender and BMI (all P ＜0.01). Multivariate regression analysis demonstrated that HOMA-IR was independently correlated with TBil and DBIi levels (β = -0.400, P < 0.01). Conclusion: MHO group harbors increased bilirubin level compared with MUHO group. HOMA-IR was independently correlated with TBil and DBIi levels.